2018
DOI: 10.1371/journal.pone.0204749
|View full text |Cite
|
Sign up to set email alerts
|

Where communities intermingle, diversity grows – The evolution of topics in ecosystem service research

Abstract: We analyze how the content of ecosystem service research has evolved since the early 1990s. Conducting a computational bibliometric content analysis we process a corpus of 14,118 peer-reviewed scientific article abstracts on ecosystem services (ES) from Web of Science records. To provide a comprehensive content analysis of ES research literature, we employ a latent Dirichlet allocation algorithm. For three different time periods (1990–2000, 2001–2010, 2011–2016), we derive nine main ES topics arising from cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 48 publications
(81 reference statements)
9
55
1
Order By: Relevance
“…The word cloud shows that the term "ecosystem services" is the highest co-occurring keyword, followed by "biodiversity" and "conservation." Our results support the recent findings of a previous paper that explored publications in ecosystem services research (Droste et al 2018). Ecosystem services, i.e., the benefits we receive from nature, is closely linked to natural capital, i.e., the stock natural resources.…”
Section: Crossing Disciplines and Subject Areassupporting
confidence: 91%
“…The word cloud shows that the term "ecosystem services" is the highest co-occurring keyword, followed by "biodiversity" and "conservation." Our results support the recent findings of a previous paper that explored publications in ecosystem services research (Droste et al 2018). Ecosystem services, i.e., the benefits we receive from nature, is closely linked to natural capital, i.e., the stock natural resources.…”
Section: Crossing Disciplines and Subject Areassupporting
confidence: 91%
“…Of the 2,497 study hits, 1,632 (65%) were ES assessment studies. Reviewing the remaining 1,632 studies revealed that a large portion (65%) embraced social sciences and humanities perspectives, mostly in combination with economic and/or ecological assessments; congruent with results in Droste et al (2018). Much of this literature is recent (appearing within approximately the last 4-5 years), suggesting that social sciences and humanities studies are increasing in ES research.…”
Section: Social Sciences and Humanitiesmentioning
confidence: 76%
“…More specifically, scholars have identified multiple concerns related to connecting ES science in particular to decision‐making, such as the importance of institutions equipped to support the use of ES data (Daily & Matson, ) and the multiple ways that ES data are used in policy processes (McKenzie et al, ). In general, ES scholars increasingly attend to ‘what happens’ with ES science; a computer‐aided review of over 14,000 ES publications found that since the ES term first entered widespread use in the 1990s, discussion of governance has increased markedly in ES‐related peer‐reviewed publications (Droste, D’Amato, & Goddard, ).…”
Section: Discussionmentioning
confidence: 99%